Studies on selection of elite lines of CI-37 seedling progenies of cardamom (Elettaria cardamomum Maton) - HOSMANI, V S KORIKANTHIMATH, M J MATHEW, RAVINDRA MULGE, RAJENDRA HEGDE, M M (Journal of Spices and Aromatic Crops, 1999)
Studies were carried out at Chettalli (Karnataka, India) to select high yielding accessions (lines) of cardamom (Elettaria cardamomum) from seedling progenies of CI-37 in a cardamom plantation and also to identify plants for earliness (yielding) coupled with high yield potential. Among the 275 high yielding accessions selected, 49 entries (17.8% of total entries) were classified as high yielders with a mean yield of 6537.01 g wet capsules/clump. High variability for total yield and Bartlet Index of earliness for yield was observed. The yield per clump varied from 325 to 7555 g wet capsules/clump. Entry No. 186 was identified to be a high yielding early type having the highest Bartlet Index of 0.7084950 with a total yield of 5156 g wet capsules/clump.